Preliminary paleoecological insights from the Pliocene avifauna of Kanapoi, Kenya: Implications for the ecology of Australopithecus anamensis. Issue 140 (March 2020) - Field, Daniel J.
Abstract: Fossil bird remains from the Pliocene hominin-bearing locality of Kanapoi comprise >100 elements representing at least 10 avian families, including previously undescribed elements referred to the 'giant' Pliocene marabou stork Leptoptilos cf. falconeri . The taxonomic composition of the Kanapoi fossil avifauna reveals an assemblage with a substantial aquatic component, corroborating geological evidence of this locality's close proximity to a large, slow-moving body of water. Both the taxonomic composition and relative abundance of avian higher-level clades at Kanapoi stand in stark contrast to the avifauna from the slightly older (∼4.4 Ma vs. 4.2 Ma) hominin-bearing Lower Aramis Member of Ethiopia, which has been interpreted as representing a mesic woodland paleoenvironment far from water. In general, the taxonomic composition of the Kanapoi avifauna resembles that from the Miocene hominoid-bearing locality of Lothagam (though Kanapoi is more diverse), and the aquatic character of the Kanapoi avifauna supports the idea that the environmental conditions experienced by Australopithecus anamensis at Kanapoi were markedly different from those experienced by Ardipithecus ramidus at Aramis. Additionally, the relative abundance of marabou stork ( Leptoptilos ) remains at Kanapoi may suggest a longstanding commensal relationship between total-clade humans and facultatively scavenging marabous. Additional avian remains from nearby fossil localities (e.g., the Nachukui Formation), ranging in age from 3.26 to 0.8 Ma, reveal the long-term persistence of an aquatic avifauna in the region.